An update on treatment options for pancreatic adenocarcinoma. (September 2019) - Lambert, Aurélien; Schwarz, Lilian; Borbath, Ivan; Henry, Aline; Van Laethem, Jean-Luc; Malka, David; Ducreux, Michel; Conroy, Thierry
Pancreatic cancer is one of the most lethal solid organ tumors. Due to the rising incidence, late diagnosis, and limited treatment options, it is expected to be the second leading cause of cancer deaths in high income countries in the next decade. The multidisciplinary treatment of this disease depends on the stage of cancer at diagnosis (resectable, borderline, locally advanced, and metastatic disease), and combines surgery, chemotherapy, chemoradiotherapy, and supportive care. The landscape of multidisciplinary pancreatic cancer treatment is changing rapidly, especially in locally advanced disease, and the number of treatment options in metastatic disease, including personalized medicine, innovative targets, immunotherapy, therapeutic vaccines, adoptive T-cell transfer, or stemness inhibitors, will probably expand in the near future. This review summarizes the current literature and provides an overview of how new therapies or new therapeutic strategies (neoadjuvant therapies, conversion surgery) will guide multidisciplinary disease management, future clinical trials, and, hopefully, will increase overall survival.